Pemanfaatan Tumbuhan Melalui Edukasi Ecoprint Yang Ramah Lingkungan Di Kecamatan Air Joman - Hommy Dorthy Ellyany Sinaga; Yessica Siagian; Desma Erica Maryati M. (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
Community service for women of family welfare development, usually named women of PKK. In Air Joman district, Asahan, is planned to provide training on the use of plants through eco-print education (i.e., leaf prints on cloth), which are environmentally eco-friendly to improve their creativity and skills. The participants were taught to recognize plants that can be used in eco-print techniques and understand the process of scouring and mordanting. Furthermore, the other objective is that they will be able to make plant trace motifs in the form of leaves and flowers on cloth and make it have a higher selling value for fashion needs and supporters. This training activity was carried out in direct practice by participants in June and July 2022 in 3 groups of 10. The first meeting will be presented to all groups using the offline direct exposure method. An eco-print expert will handle the training. The second meeting to the seventh meeting will be such a kind of workshop activity. The participants will be grouped into three groups and practice the process. Training on the using plants through eco-friendly education in the Air Joman district has giving an impact of knowing more plants that can be use in eco-print, and also increase the ability to produce the higher value of eco-printing product.